2016
DOI: 10.14202/vetworld.2016.875-881
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of virulence genes of Streptococcus equi subsp. equi and Streptococcus equi subsp. zooepidemicus in equines

Abstract: Aim:The aim was to determine the occurrence of streptococci in equines in Jammu (R. S. Pura, Katra), characterization of Streptococci equi subsp. equi and Streptococcus equi subsp. zooepidemicus with respect to their virulence traits and to determine antibiotic sensitivity pattern of virulent Streptococcus isolates.Materials and Methods:A total of 96 samples were collected from both clinically affected animals (exhibiting signs of respiratory tract disease) and apparently healthy animals and were sent to labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
3
13
0
Order By: Relevance
“…This type of anaemia shows an increase in MCV and decrease in MCHC (Kahn andScott, 2010, Okolo et al, 2015). The findings in the present study are in agreement with those of Basavraj et al (2012), who showed that diclofenac sodium at 9.5 mg/kg orally administered for 28 days in albino Swiss mice induced significant decreases in Hb and PCV values. Similar findings were observed by El-Maddawy and El-Ashmawy (2013), who reported that administration of diclofenac sodium to adult male rats at a dose of 13.5 mg/kg by i/m route for 14 days induced significant reduction in Hb, PCV, RBC and WBC values compared to the control.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This type of anaemia shows an increase in MCV and decrease in MCHC (Kahn andScott, 2010, Okolo et al, 2015). The findings in the present study are in agreement with those of Basavraj et al (2012), who showed that diclofenac sodium at 9.5 mg/kg orally administered for 28 days in albino Swiss mice induced significant decreases in Hb and PCV values. Similar findings were observed by El-Maddawy and El-Ashmawy (2013), who reported that administration of diclofenac sodium to adult male rats at a dose of 13.5 mg/kg by i/m route for 14 days induced significant reduction in Hb, PCV, RBC and WBC values compared to the control.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are similar to that of El-Maddawy & ElAshmawy (2013), who reported that diclofenac sodium causes hepatotoxicity, inducing a rise in liver enzymes such as AST, ALT & ALP, resulting in hepatitis. Our findings are also in agreement with Basavraj et al (2012), who reported that administration of diclofenac sodium at the dose of 9.5 mg/kg per os for 28 days in albino Swiss mice induces significant increases in AST and ALT values.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…equi comprised of pathogenic strains, and paraphyletic S. equi subsp. zooepidemicus , that are a part of the normal microphlora in horses (Javed et al, 2016 ) (Figures 3A,E , Supplementary Table S2 ). The weak criterion partitions S. equi into two groups exactly matching the subspecies.…”
Section: Resultsmentioning
confidence: 97%
“…However, unlike SEZ, SEE does not colonize the nasopharynx of healthy animals [74]. Antibiotic susceptibility studies have shown that most SEE have broad susceptibility to antibiotics [68]. SER is a rarely isolated species.…”
Section: Streptococcus Parauberismentioning
confidence: 99%